PENGARUH MEDIA PEMBELAJARAN TERHADAP MOTIVASI BELAJAR EKONOMI MASA PANDEMI COVID-19 PADA SISWA KELAS X IPS 2 DI SMA NEGERI 2 PANGKALAN KERINCI TAHUN AJARAN 2021 - Intan Masriani (Universitas Negeri Medan, 2021)
Abstract: The Influence Of Learning Media On Motivation To Study Economics During The Covid-19 Pandemic In Class X IPS 2 Students At SMA Negeri 2 Pangkalan Kerinci For The 2021 Academic Year. This study aims to improve students' practical learning outcomes in the application of single-phase electrical installations, here it is required to apply teaching aids through the application of the posing problem learning model in class XI Electrical Power Installation Engineering at Private Vocational Schools of Muhammadiyah Pekanbaru. August to September 2018. The subjects of this study were students of class XI Electrical Power Installation Engineering at SMK Muhammadiyah I Pekanbaru, totaling 25 people, consisting of 25 men. The data in this study were collected using learning outcomes tests which were scored based on indicators. learn the practice of single-phase electrical installation. The completeness of student learning outcomes is by comparing the basic scores with the Daily Deuteronomy I and Daily Deuteronomy II on the material for the application of single-phase electrical installations. After conducting research with two cycles, the application of the posing problem learning model can improve learning outcomes of single-phase electrical installation practices where at the end of the first cycle of action there are 25 students who have completed or 78% with an average student learning outcome or student understanding of 65.25, then increased in the second daily test with a total of 24 students or 83.25% completed with the average student learning outcomes or concept understanding increased to 81.45 at the end of the second cycle of action. the practice of single-phase electrical installation using teaching aids for class XI students of electrical power installation techniques at the Muhammadiyah I Pekanbaru Private Vocational School on the material of applying single-phase electrical installations.Keywords: learning outcomes, practice, posing problems, electrical installation Abstrak: Pengaruh Media Pembelajaran Terhadap Motivasi Belajar Ekonomi Masa Pandemi Covid-19 Pada Siswa Kelas X IPS 2 di SMA Negeri 2 Pangkalan Kerinci Tahun Ajaran 2021. The Influence of Learning Media on Students' Learning Motivation in Class X IPS 2 Economics Subject at SMA Negeri 2 Pangkalan Kerinci. SMA Negeri 2 Pangkalan Kerinci. To achieve this goal, the researchers used data collection techniques through observation, questionnaires, and documentation with a sample of 35 people. The data was processed using quantitative analysis to determine the effect of learning media on students' learning motivation. The results showed that the level of use of learning media was categorized as good in terms of indicators of visual media, audio media and audio visual media. The level of student learning motivation is classified as very high in terms of indicators that excite students, provide realistic expectations, provide incentives, and direct student behavior. The results of the analysis and hypothesis testing indicate that there is a significant effect of learning media on the learning motivation of students in Class X Social Sciences 2 Economics at SMA Negeri 2 Pangkalan Kerinci with a low level of influence. Keywords: media use, to increase learning motivation motivasi